2005
DOI: 10.1191/0267659105pf800oa
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin is useful whereas C-reactive protein is not, to predict complications following coronary artery bypass surgery

Abstract: A postoperative serum PCT concentration of >0.5 ng/mL is highly suggestive of a postoperative complication. CRP changes do not contribute to predictive information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
0
16
0
4
Order By: Relevance
“…Several trials have proved the poor diagnostic value of CRP in the postoperative period especially if compared with PCT. Macrina et al [2] used CrP to follow septic patients and found that CrP was unable to predict the outcome of disease or severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several trials have proved the poor diagnostic value of CRP in the postoperative period especially if compared with PCT. Macrina et al [2] used CrP to follow septic patients and found that CrP was unable to predict the outcome of disease or severity.…”
Section: Discussionmentioning
confidence: 99%
“…After surgery C-reactive protein (CrP) is widely used to monitor the postoperative course, especially with regard to infection. However, several trials showed a lower sensitivity in the (early) postoperative period for CrP in comparison to procalcitonin (PCT) that has become increasingly popular as a marker of infection after surgical procedures [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…C-reactive protein (CRP) levels increase postoperatively, peaking between postoperative days one and three and remaining elevated up to the second week postoperatively [29,30,35,54]. irrespective of the extent of surgery [33,34,36,38,42,45,46,54]. Levels of interleukin-6 (IL-6), another marker of immune system activation, also increase postoperatively [34,41,46,48,50,55,56].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported higher PCT levels after cardiac surgery in infected compared with non-infected patients [33,35-38,41,45,57,58]. Importantly, PCT levels remained elevated in the first week postoperatively [35,37,38].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation